Making Inclusive Education a Reality : It is not Just a Formality - Devendra, Kiran (THE PRIMARY TEACHER, 2008)
Each child is special. It is the responsibility of every citizen to help children realise their potential to the fullest and groom them to be contributing citizens of this country. A special emphasis has been given by SSA to reach out to Children with Special Needs (CWSNs) not only by way of providing ramps, wheelchairs, spectacles, hearing aids etc. but also by providing home based education to those who have severe disabilities. This article throws light on the efforts of the stakeholders in SSA in two districts of Punjab and a private school in Ambala Cantt. Haryana, where the lives of children with multiple physical challenges have changed with the support of their teachers, parents and peers.